دافعية التعلم في ضوء الإسلام: Learning Motivation from Islamic Perspective - Faizah binti Majahar; Rahmah Binti Ahmad H. Osman; Siti Nurul Afifah binti Pauzi; Siti Adibah binti Aziz (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تعد دافعية التعلم من إحدى العناصر المهمة في مساعدة الطلبة للوصول إلى الأهداف التعليمية المرجوة وتحقيق التعلم الفعال، وثمة عوامل تؤثر على دافعية التعلم. وتتوافر الدراسات العديدة حول هذه القضية إلا أن معظمها تركز على الجوانب المادية وتهمل الجوانب الروحية بسبب اعتمادها على النظريات الغربية. فيهدف هذا البحث إلى التعرف على دافعية التعلم لدى طلبة الجامعة من منظور الإسلام ومعرفة الجوانب الروحية فيها وكشف العلاقة بينهما. وتوصل البحث إلى أن الجوانب الروحية تؤدي دورا هاما في تعزيز الدافعية للتعلم لدى الطلبة وابتعادهم عن أعمال سيئات مخالفة للتعاليم الإسلامية. Abstract Learning motivation is one of the important elements in helping students reaching their desired educational goals and promoting effective learning. There are many studies on factors that affect learning motivation but most of them focused on the material aspects and neglected the spiritual aspects due to their dependence on Western theories. Therefore, this study is designed to identify the learning motivation from the perspective of Islam among university students, the spiritual aspects in it and to uncover the relationship between them. The results indicated that spiritual aspects play an important role in enhancing students’ learning motivation and help them staying away from evil deeds that are not in line with Islamic teachings.